2017
DOI: 10.1038/srep43662
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose penicillin exposure in early life decreases Th17 and the susceptibility to DSS colitis in mice through gut microbiota modification

Abstract: Antibiotic exposure in early life can lead to a significant change of the gut microbiota and may contribute to later onset of inflammatory bowel disease (IBD). However, the relationship between early-life antibiotic treatment and IBD is ambiguous, according to contradicting results of epidemiologic studies. In the present study, we demonstrated that low-dose penicillin pre-treatment had a unique protective effect against mouse colitis induced by dextran sodium sulfate (DSS). Low-dose penicillin also suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 62 publications
2
49
0
Order By: Relevance
“…This phenomenon was consistent with findings in a previous study, which demonstrated distinct expansion in the abundance of SFB in the small intestines of mice lacking activation-induced cytidine deaminase and immunoglobulin A (7,58). In addition, treatment with antibiotics inhibited colo-nization by SFB (59). These results hint that loss of selective stressors, including immune pressure or antibiotics, may enable overcolonization of SFB in the intestine.…”
supporting
confidence: 92%
“…This phenomenon was consistent with findings in a previous study, which demonstrated distinct expansion in the abundance of SFB in the small intestines of mice lacking activation-induced cytidine deaminase and immunoglobulin A (7,58). In addition, treatment with antibiotics inhibited colo-nization by SFB (59). These results hint that loss of selective stressors, including immune pressure or antibiotics, may enable overcolonization of SFB in the intestine.…”
supporting
confidence: 92%
“…Prior work has shown that SFB colonization can be modulated by diet, (138,139) probiotics, (140) and antibiotics. (141)(142)(143) This highlights the potential for the development of noninvasive clinical interventions in the pediatric gut microbiome, which could be utilized to support postpubertal skeletal growth and maturation. Although SFB colonizes humans and upregulates T H 17 pathway genes, (24,31) it is important to note other commensals have been shown to clinically induce T H 17/IL17A-mediated immunity.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Some case reports provide evidence that SFB could be detected at certain inflammatory sites both in ulcerative colitis (UC) and Chrons disease (CD) patients, while depletion of SFB by penicillin decreased Th17 and susceptibility to Dextran Sodium Sulfate (DSS)-induced colitis in mice. 47 On the other hand, SFB colonization could be important for the defense against bacterial pathogens, for instance, antibiotic use reduced SFB and Th17 cell numbers, decreasing resistance against intestinal pathogen Citrobacter rodentium (C. rodentium) infection. In contrast, colonization of mice with SFB conferred higher resistance to C. rodentium and was correlated with increased expression of genes associated with inflammation and antimicrobial defenses.…”
Section: Microbiota Shapes the Development Of The Immune System And Hmentioning
confidence: 99%